Pupillary response reflects attentional modulation to sound after emotional arousal - Satoshi Nakakoga (Nature Portfolio, 2021)
Abstract There have been various studies on the effects of emotional visual processing on subsequent non-emotional auditory stimuli. A previous study with EEG has shown that responses to deviant sounds presented after presenting negative pictures collected more attentional resources than those for neutral pictures. To investigate such a compelling between emotional and cognitive processing, this study aimed to examined pupillary responses to an auditory stimulus after a positive, negative, or neutral emotional state was elicited by an emotional image. An emotional image was followed by a beep sound that was either repetitive or unexpected, and the pupillary dilation was measured. As a result, we found that the early component of the pupillary response to the beep sound was larger for negative and positive emotional states than the neutral emotional state, whereas the late component was larger for the positive emotional state than the negative and neutral emotional states. In addition, the peak latency of the pupillary response was earlier for negative than neutral or positive images. Further, to compensate for the disadvantage of low-temporal resolution of the pupillary data, the pupillary responses were deconvoluted and used in the analysis. The deconvolution analysis of pupillary responses confirmed that the responses to beep sound were more likely to be modulated by the emotional state rather than being influenced by the short presentation interval between the images and sounds. These findings suggested that pupil size index modulations in the compelling situation between emotional and cognitive processing.